Pseudomonas aeruginosa-derived extracellular vesicles enhance macrophage aerobic glycolysis that fuels inflammation - Li, Chun; Peng, Jing; Xiao, Lihua; Wu, Haiying; Chen, Jing; Chen, Nian (Frontiers in Microbiology, 2025)
Outer membrane vesicles (OMVs) derived from Pseudomonas aeruginosa drive inflammation by metabolically reprogramming macrophages to favor aerobic glycolysis. This study shows that OMVs trigger this metabolic shift via Toll-like receptors 2 and 4 (TLR2/4)-dependent activation of the phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) signaling pathway. OMV-stimulated macrophages exhibited increased glucose uptake, lactate production, and expression of key glycolytic enzymes, resulting in a higher extracellular acidification rate and a lower oxygen consumption rate. Inhibition of the PI3K/Akt pathway reversed these metabolic changes. Crucially, this metabolic reprogramming was required for OMV-induced secretion of pro-inflammatory cytokines, as inhibition of glycolysis via 2-deoxy-D-glucose treatment attenuated the inflammatory response both in vitro and in vivo. These findings reveal that P. aeruginosa OMVs control metabolism in macrophages through the TLR2/4-PI3K/Akt axis to promote a pro-inflammatory state and identifies glycolysis as a potential therapeutic target for bacteria-associated inflammatory diseases.